How to Support Residential Energy Conservation Cost-Effectively? An analysis of Public Financial Schemes in France - Bettina Chlond; Claire Gavard; Lisa Jeuck (Environmental and Resource Economics, 2023)
We compare the performance of four types of support schemes aimed at improving residential energy efficiency in France: the income tax credit, a grant scheme, the reduction of the value-added tax, and the White Certificates. We use the TREMI dataset which covers close to 14,000 households that conducted conservation works. To address self-selection bias, we use a double-robust inverse probability weighting estimator. We assess the effect of the adoption of each scheme on the funding acquired, the private and total investment, and the reduction of the household energy expenses. For each scheme, we use the estimates to deduct its cost-effectiveness, the involved redistribution, and its ability to trigger additional investment in energy conservation works. We find funding from the schemes to reduce energy expenses most cost-effectively via the White Certificates. Redistribution is neutral for each of the four schemes: higher and lower income households equally benefit from them.
Keywords: H23; Q58; Q84; 330; Energy efficiency; Energy conservation; Residential retrofits; Cost-effectiveness; Redistribution; Inverse probability weighting